The prosecutor as philosophical and legal subject ininformational law - Haydai, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In the article, the author improved the approach to the essence of the subject of information law as a legal embodiment of a person with information rights, duties and information culture. The author substantiated, that the prosecutor, as a subject of information law, doesn’t exist for working with information, and but information activities, which is implemented by the prosecutor to law-governed state goals achieve the goals and functions of the prosecutor’s office in a law-governed state and society goal. The author used the approach of «subjectivization», which mean, that the application of legal phenomenology methods is based on the departure of the classical sense of concepts, that are associated with its formal interpretation in the normative acts, and, especially, in the internal sense. As sources of the category «prosecutor - the subject of information law», in article is taken into account legal norms-goals and normsprinciples, which are abstracted from a particular type of relationship and make it possible to find out a more general place of the phenomenon in the legal system as a whole.